Employee Turnover and Firm Performance: Large-Sample Archival Evidence - Li, Qin; Lourie, Ben; Nekrasov, Alexander; Shevlin, Terry (Management Science, 2022)
Employee turnover is a significant cost for businesses and a key human capital metric, but firms do not disclose this measure. We examine whether turnover is informative about future firm performance using a large panel of turnover data extracted from employees’ online profiles. We find that turnover is negatively associated with future financial performance (one-quarter ahead return on assets and sales growth). The negative association between turnover and future performance is stronger for small firms, for young firms, for firms with low labor intensity, when the local labor market is tight, and when the firm is trying to replace departing employees. The negative association disappears when turnover is very low, suggesting that a certain amount of turnover can be beneficial. Consistent with the concern that turnover increases operational uncertainty, we find a positive association between turnover and the uncertainty of future financial performance. Finally, we find a significant association between turnover and future stock returns, suggesting that investors do not fully incorporate turnover information. Our findings answer the call from the Securities and Exchange Commission to determine the importance of turnover disclosure. This paper was accepted by Brian Bushee, accounting.